2010
DOI: 10.1111/j.1369-1600.2010.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

MAOA genotype, family relations and sexual abuse in relation to adolescent alcohol consumption

Abstract: The aim of the present study was to investigate MAOA gene-environment (G*E) interactions in relation to adolescent alcohol consumption. In the county of Västmanland, Sweden, all 17-18-year-old students were asked to complete an anonymous questionnaire and provide a saliva sample during class hours. A total of 2263 students completed the questionnaire (77.4%) and a saliva sample was provided by 2131 participants. Failed MAOA u-variable number of tandem repeats (VNTR) genotype analyses and internal non-responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 50 publications
7
52
0
1
Order By: Relevance
“…Similar results were found by Aslund et al (2011) and Nilsson et al (2011) (Table 1) examining, respectively, delinquent behaviour and high alcohol consumption. MAOA polymorphism was also found to enhance depressive symptoms but only among extensively maltreated youth (i.e.…”
Section: -25supporting
confidence: 87%
“…Similar results were found by Aslund et al (2011) and Nilsson et al (2011) (Table 1) examining, respectively, delinquent behaviour and high alcohol consumption. MAOA polymorphism was also found to enhance depressive symptoms but only among extensively maltreated youth (i.e.…”
Section: -25supporting
confidence: 87%
“…However, a recent study showed increased mRNA expression in lymphoblasts of patients with a history of alcohol dependence [43]. Knocking out Maoa in early development has a strong impact on serotonin levels, which may normalize with age [66], and a similar effect that dissipates with age may also occur with 5-HTT.…”
Section: -Htt Gene In Rats and Mice Results In Decreasedmentioning
confidence: 98%
“…Further, DNA methylation at selected cytosine-phosphateguanine sites (CpG) of the 5-HTTLPR was reported to be higher among females than males [42]. Only three studies analyzed GxE interactions separately among males and females and two found a sex difference [33,34,36], as has been shown for other genetic markers [43]. Ethnicity is another important factor as differences have been reported in the frequencies of the 5-HTTLPR genotype and in alcohol use.…”
Section: Summary Of Gene-by-environment Findings In Human Studiesmentioning
confidence: 99%
“…Gene-environment interactions have been reported for the serotonin transporter ( 5-HTT ) [3235], the dopamine receptor ( DRD2 )/ankyrin repeat and kinase domain containing 1 ( ANKK1 ) [3638], catechol-O-methyltransferase ( COMT ) [39, 40], monoamine oxidase ( MAOA ) [4143], GABA A receptor ( GABRA2 ) [44], corticotrophin releasing hormone receptor 1 ( CRHR1 ) [4548]. …”
Section: Reviewmentioning
confidence: 99%